Sensitivity of Helicobacter pylori detection by Giemsa staining is poor in comparison with immunohistochemistry and fluorescent in situ hybridization and strongly depends on inflammatory activity. Issue 4 (12th April 2017) - Kocsmár, Éva; Szirtes, Ildikó; Kramer, Zsófia; Szijártó, Attila; Bene, László; Buzás, György Miklós; Kenessey, István; Bronsert, Peter; Csanadi, Agnes; Lutz, Lisa; Werner, Martin; Wellner, Ulrich Friedrich; et al.
Abstract: Background: Conventional stainings (including H&E and special stains like Giemsa) are the most widely applied histopathologic detection methods of Helicobacter pylori (HP). Materials and Methods: We aimed to compare the diagnostic performance of Giemsa staining with immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH) on a monocentric cohort of 2896 gastric biopsies and relate results to histologic alterations in order to find such histopathologic subgroups in which these methods underperform. All cases were categorized regarding presence or absence of chronic gastritis, inflammatory activity, and mucosal structural alterations. Results: Giemsa revealed 687 cases (23.7%), IHC 795 cases (27.5%), and FISH 788 cases (27.2%) as being HP positive. Giemsa showed significantly lower overall sensitivity (83.3%) compared to IHC (98.8%) and FISH (98.0%). Moreover, the sensitivity of Giemsa dramatically dropped to 33.6% in the nonactive cases. We found that sensitivity of Giemsa strongly depends on HP density and, accordingly, on the presence of activity. Structural alterations (intestinal metaplasia, atrophy, etc.) had only no or weak effect on sensitivity of the three stainings. Both IHC and FISH proved to be equally reliable HP detecting techniques whose diagnostic performance is minimally influenced by mucosal inflammatory and structural alterations contrary to conventional stainings. Conclusions: We highly recommend immunohistochemistry for clinically susceptible, nonactive chronic gastritis cases, if the conventional stain‐based HP detection is negative. Moreover, we recommend to use IHC more widely as basic HP stain. Helicobacter pylori FISH technique is primarily recommended to determine bacterial clarithromycin resistance. Furthermore, it is another accurate diagnostic tool for HP.